2006
DOI: 10.1186/1748-717x-1-13
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of intensity-modulated, conformal, and four-field pelvic radiotherapy boost plans for gynecologic cancer: a retrospective planning study

Abstract: Purpose: To evaluate intensity-modulated radiation therapy (IMRT) as an alternative to conformal radiotherapy (CRT) or 4-field box boost (4FB) in women with gynecologic malignancies who are unsuitable for brachytherapy for technical or medical reasons.Methods: Dosimetric and toxicity information was analyzed for 12 patients with cervical (8), endometrial (2) or vaginal (2) cancer previously treated with external beam pelvic radiotherapy and a CRT boost. Optimized IMRT boost treatment plans were then developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 38 publications
4
22
0
Order By: Relevance
“…In our study it was found that 30% of the volume of the rectum received about 70% of the prescribed dose by the IMRT field while in CRT 30% of the rectal volume received 95%of the dose, this is in concordance to what was reported by Philip Chan et al 2006 [5] where there was rectal volume reduction by about 22% on using the 8 fields IMRT.…”
Section: Regarding the Rectal Dosesupporting
confidence: 92%
See 3 more Smart Citations
“…In our study it was found that 30% of the volume of the rectum received about 70% of the prescribed dose by the IMRT field while in CRT 30% of the rectal volume received 95%of the dose, this is in concordance to what was reported by Philip Chan et al 2006 [5] where there was rectal volume reduction by about 22% on using the 8 fields IMRT.…”
Section: Regarding the Rectal Dosesupporting
confidence: 92%
“…In our study it was found that the IMRT technique reduces the volume of the bladder receiving the dose by about 30% than that of the 3DCRT which is in concordance to what was reported by Philip Chan et al 2006 [5] who reported reduction in the bladder volume by 19% on using the 8 fields IMRT.…”
Section: Regarding Bladder Dosesupporting
confidence: 92%
See 2 more Smart Citations
“…IMRT and 3-dimensional conformal radiotherapy (3DCRT) are now widely used radiotherapy techniques for various cancers and have been shown to be acceptable alternatives to brachytherapy for the treatment of gynecologic malignancies [5,9]. …”
Section: Discussionmentioning
confidence: 99%